1995
DOI: 10.1097/00000658-199503000-00010
|View full text |Cite
|
Sign up to set email alerts
|

The Natural History of Appendicitis in Adults A Prospective Study

Abstract: This prospective study identifies that delay in presentation accounts for the majority of perforated appendices. Clinical evaluation is effective for identifying patients with more advanced disease. Indiscriminate appendectomy as an attempt to decrease perforation is not supported by these data. Hospital perforation rates likely reflect patient factors, illness attitude, and access to medical care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
162
2
14

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(194 citation statements)
references
References 2 publications
16
162
2
14
Order By: Relevance
“…With increasing age there is an increasing number of potential differential diagnoses that could delay a correct diagnosis. Late presentation may also be a contributing factor 29 . It has been suggested that the high proportion of perforations in the elderly is a mere consequence of the relatively low incidence of NPA among these patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…With increasing age there is an increasing number of potential differential diagnoses that could delay a correct diagnosis. Late presentation may also be a contributing factor 29 . It has been suggested that the high proportion of perforations in the elderly is a mere consequence of the relatively low incidence of NPA among these patients 30 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The mortality risk is <1% in non-perforated appendicitis, 5 but increase to 4%-8% in the elderly. 1,2,5,6 Delay before appendectomy is associated with increase in perforation rate.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] The mortality risk is <1% in non-perforated appendicitis, 5 but increase to 4%-8% in the elderly. 1,2,5,6 Delay before appendectomy is associated with increase in perforation rate. 7,8 Acute perforated appendicitis is still associated with significant morbidity and mortality in the elderly patients and we still need to strive for early detection of perforation.…”
Section: Introductionmentioning
confidence: 99%
“…Appendicular perforation ranges 50-90% in various series. 6,7 The importance of laboratory investigations like White Blood Cell (WBC) counts and C-reactive protein (CRP) etc. values has been stressed to supplement the clinical diagnosis and to reduce the frequency of unnecessary appendicectomy.…”
Section: Introductionmentioning
confidence: 99%